FEMALE PARTICIPATION IN THE STATE IN MUSTAPHA AND MACBETH: A HEGELIAN APPROACH - Gülter, Işıl Şahin (My University, 2018)
Queen Elizabeth’s reign informs dramatists to deal with the themes of power and politics in this era,since the sovereign’s gender is one of the fundamental social and political considerations of Elizabethanperiod. The English display an ambivalent reaction to the idea of woman ruler, as a ruler is always identifiedwith masculinity. Queen Elizabeth’s reign arouses a vague anxiety among the English people who perceivean inherent danger within female rule. In this context, this study aims to analyze perception of inherentdanger within female rule in Fulke Greville’s Mustapha (1594) and W. Shakespeare’s Macbeth (1606) byfocusing on the representation of female participation in state affairs in the light of Hegel’s construction ofthe state. According to Hegel, nature assigns man to the state, and woman to the family; man maintains hispower in public affairs while the woman is expected to fulfill the responsibility of training children to becitizens of the state rather than participating in public affairs. In Mustapha, Greville sets his play in theOttoman state and depicts Rossa (Hurrem Sultan) as an ambitious, manipulative, and intriguing character.Similarly in Macbeth, Shakespeare stages Lady Macbeth as a power-hungry and intriguing character. Rossa(Hurrem Sultan) and Lady Macbeth’s preference of political to familial is depicted as unnatural by theirnature that results in disorder for the state. This study aims to demonstrate that Greville and Shakespearerepresent female participation in the state as a disruptive force in the light of Hegel’s construction of thestate.
Keywords: Edebiyat